Faktor-Faktor Pemborosan Material Pekerjaan Arsitektural Pada Proyek Perumahan Griya Gigeh Putroe Ijo - Rita Fazlina; Rinaldy Rinaldy; Raina Parmitalia Dinda; Zulyaden Zulyaden; Fadli Idris; Astiah Amir; Rezqi Malia (VOCATECH: Vocational Education and Technology Journal, 2025)
Abstract In residential construction, one of the major issues encountered is material waste, referring to the excessive use or presence of materials that do not add value to the construction work. There are several causes of material waste in construction, including the overconsumption of resources, the consolidation and expansion of technical specifications across multiple buildings, the reduction in material quality due to handling processes or mobilization errors, the deterioration of materials caused by weather conditions or improper storage, the lack of documentation for materials received and utilized, construction debris, as well as surplus materials resulting from preparation and finishing works.This study focuses on analyzing the factors that influence material waste in architectural works and identifying the dominant factors contributing to material waste in the architectural phase of the Griya Gigeh Putroe Ijo housing project, using the index method. Based on the research findings, the most dominant factor affecting material waste in architectural works is the variable Residual/Excess Material and Implementation, which consists of indicators such as worker errors, adverse weather conditions, unusable material offcuts, incorrect cutting dimensions, and inappropriate material orders resulting from inaccurate estimations. This is supported by the highest mean value of 4.86. The calculation using the index method indicates that the percentage value of the material waste index factor in architectural works is 92.04%, which falls within the 90%–100% range. Therefore, it can be categorized as Highly Influential in causing material waste in architectural activities within the Griya Gigeh Putroe Ijo housing development project, located in Meulaboh City, West Aceh Regency.Keywords:Waste; Material; Architectural Work; Housing Project; Griya Gigeh Putroe Ijo.Abstrak Dalam konstruksi perumahan, salah satu masalah yang ditemui adalah pemborosan material atau jumlah material yang berlebihan yang tidak memberikan nilai tambah pada pekerjaan. Terdapat beberapa macam penyebab pemborosan material dalam konstruksi, diantaranya meliputi konsumsi sumber daya yang berlebihan, penyatuan dan pengembangan spesifikasi teknis dari sejumlah bangunan, penurunan mutu material efek proses penanganan atau kesalahan mobilisasi, penurunan mutu material karena cuaca dan penyimpanan logistik yang tidak sesuai, kurangnya dokumentasi material yang diterima dan digunakan, limbah konstruksi, serta kelebihan material dari pekerjaan persiapan dan penyelesaian. Studi ini difokuskan pada analisis faktor-faktor yang mempengaruhi pemborosan material dalam pekerjaan arsitektur dan mengidentifikasi faktor dominan yang mempengaruhi pemborosan material dalam pekerjaan arsitektur pada proyek perumahan Griya Gigeh Putroe Ijo dengan menggunakan metode indeks. Berdasarkan hasil penelitian, faktor yang paling dominan mempengaruhi pemborosan material dalam pekerjaan arsitektur adalah variabel Sisa/Kelebihan Material dan Pelaksanaan, yang terdiri dari indikator-indikator seperti kesalahan yang disebabkan oleh pekerja, cuaca buruk, potongan material yang tidak dapat digunakan, kesalahan dimensi pemotongan, dan pemesanan material yang salah akibat tidak sesuaikebutuhan. Hal ini dibuktikan dengan nilai mean tertinggi sebesar 4,86. Perhitungan menggunakan metode Indeks menunjukkan bahwa nilai persentase faktor indeks pemborosan material dalam pekerjaan arsitektur adalah 92,04% dalam rentang skala 90%-100%, sehingga dapat dikategorikan sebagai Sangat Berpengaruh dalam menyebabkan pemborosan material dalam pekerjaan arsitektur pada proyek pengembangan perumahan Griya Gigeh Putroe Ijo di Kota Meulaboh, Kabupaten Aceh Barat.Kata Kunci:Pemborosan; Material; Pekerjaan Arsitektural; Proyek Perumahan; Griya Gigeh Putroe Ijo.